Barriers to access to care in the implementation of telemedicine in public hospitals in Southern Ethiopia: A phenomenological qualitative study - Getachew Nigussie Bolado; Bizuayehu Atinafu Ataro; Christian Kebede Gadabo; Tamirat Ersino Kebamo; Worku Mimanu Minuta; Abenezer Duta Wolde (PLoS ONE, 2025)
Background Technological advancement has had a beneficial impact on enhancing healthcare globally. The adoption of telemedicine is a crucial component of digital health, but various obstacles have impeded its adoption in developing nations like Ethiopia. Hence, identifying these influencing factors will aid in fostering its implementation in Ethiopia. Objective To explore challenges in the implementation of telemedicine in public hospitals in southern Ethiopia. Methods This study employed a phenomenological qualitative research design and twelve healthcare professionals and six patients were purposively chosen from sixteen public hospitals in Southern Ethiopia to explore the influencing factors of the implementation of telemedicine. Data were gathered through in-depth interviews and field notes between September 10 and October 10, 2024. The data analysis was conducted using OpenCode 4.02 software, and a content thematic analysis was executed following Colaizzi’s 7-step method. Results During this study, four themes emerged, encompassing eighteen subthemes of challenges to care faced by healthcare professionals and patients during the implementation of telemedicine. These themes were administrative and managerial-related challenges, healthcare professionals-related challenges, patient-related challenges, and technology-related challenges. The most commonly raised subthemes were language and cultural barriers, adaptability, and complexity, privacy and cybersecurity, a lack of clear policies and an implementation climate, a lack of necessary resources, a lack of experience and skills, inadequate knowledge and unfavorable attitudes, poor awareness and understanding of technologies, and the high cost of devices and services. Conclusion and recommendations Healthcare professionals and patients in public hospitals in southern Ethiopia encountered challenges related to technology use, patient-related challenges, management and administrative obstacles, and issues unique to healthcare workers. These considerations shed more light on the unique challenges that healthcare providers and patients face while implementing telemedicine.